Cost Accounting Principles and Managerial Applications (Book). - Haseman, Wilber C.; Zeff, Stephen A. (The Accounting Review, 1963)
Reviews the book "Cost Accounting Principles and Managerial Applications," by Gerald R. Crowningshield.